Comparative antimycobacterial activity of some Indonesian medicinal plants against multi-drug resistant Mycobacterium tuberculosis - Maksum Radji, Marita Kurniati, Ariyani Kiranasari (Journal of Applied Pharmaceutical Science, 2015)
This study has been carried out to compare antimycobacterial activity of five selected Indonesian endogenous medicinal plants of Andrographis paniculata, Annona muricata, Centella asiatica, Pluchea indica, and Rhoeo spathacea against clinical isolate of multi-drug resistant (MDR) Mycobacterium tuberculosis. The aqueous extracts of leaves of Andrographis paniculata, Annona muricata, Centella asiatica, Pluchea indica, and Rhoeo spathacea were obtained by maceration, and the phytochemical constituents of each extract were screened. Antimycobacterial activity of aqueous plant extracts were determined by proportion methods using Lowenstein Jensen (L-J) medium. Our study exhibited that all extracts of five selected plants showed inhibited activity against Mycobacterium tuberculosis H37Rv strain and multi drug resistant (MDR) strain. The proportion inhibition of aqueous extract of Andrographis paniculata, Annona muricata, Centella asiatica, Pluchea indica, and Rhoeo spathacea, against Mycobacterium tuberculosis H37Rv strain were 100%, 82.1%, 78.5%, 100%, and 100% respectively, whereas against MDR strain were 93.7%, 50.0%, 50.0%, 100%, and 100% respectively. The phytochemical analysis showed that the extracts were predominantly contains flavonoids, alkaloids, saponins, tannins and glycosides. Pluchea indica, and Rhoeo spathacea showed good antimycobacterial activity against MDR strains and could be useful as complementary alternative therapy in combating the emergence of MDR strains of Mycobacterium tuberculosis.
Keywords: Antimycobacterial activity, MDR tuberculosis, medicinal plants, Indonesia.